Quasi-simple secondary waves in a gas of quasi-particles - Khodusov, V.D. (Вопросы атомной науки и техники, 2001)
The equations describing simple secondary waves are obtained in gas dynamics with conserved and non-conserved number of quasi-particles at interactions. The non-linearity parameter in phonon and magnon gas dynamics is found, which appears to be in its value of an order of unity. The generalized Burgers equation is obtained describing the quasi-simple secondary waves.